Sistem Pemilihan Ikan Lele Siap Panen berbasis Mikrokontroler dengan Metode K-Nearest Neighbors - Wisik Dewa Maulana; Dahnial Syauqy; Fitri Utaminingrum (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Catfish is one type of fish that is often consumed by the community, catfish is also one of the fish with high economic value. In addition to high economic value, catfish is also a fish that has a fairly fast growth. Usually catfish with the age of 3.5 - 4 months are ready to be harvested, but even though the age of catfish has entered the harvest period, not all catfish have the same size as one another. That's all caused by the greedy nature of catfish and the imbalance in the number of catfish with the size of the pond. So farmers prefer to do manual sorting to determine which catfish are ready to harvest based on weight and length. Therefore, this study aims to assist catfish farmers in sorting catfish that are ready to harvest with the help of a load cell sensor to measure weight and an ultrasonik sensor to measure length. Then the two values will be classified using the K-Nearest Neighbors method with the help of Arduino as the main system for classifying and also servo as the output of this system. This study tested the load cell and ultrasonik sensors as input for the length and weight while the classification using the K-Nearest Neighbors method got an accuracy value of 81,25% with computing time 33 ms.